The new tycoons : inside the trillion dollar private equity industry that owns everything - Kelly, Jason, 1973- (Bloomberg Press series, 2012)
Inside the Trillion Dollar Industry That Owns Everything What do Dunkin' Donuts, J. Crew, Toys "R" Us, and Burger King have in common? They are all currently or just recently were owned, operated, and controlled by private equity firms. The New Tycoons: Inside the Trillion Dollar Private Equity Industry That Owns Everything takes the reader behind the scenes of these firms: their famous billionaire founders, the overlapping stories of their creation and evolution, and the outsized ambitions that led a group of clever bankers from small shops operating in a corner of Wall Street into powerhou.